Invasive squamous cell carcinoma originating from a giant penile condyloma. (May 2017) - Sir, Emin; Gungor, Melike; Ucer, Oktay; Kebat, Tulu
In this case study, we present an unusual case with squamous cell carcinoma originating from a giant condyloma acuminata completely surrounding the penis. A 57-year-old circumcised heterosexual male patient presented with a penile lesion existing for 20 years. Incisional biopsy revealed acanthosis of the squamous epithelium. The patient was operated on under spinal anaesthesia. The lesion was resected circumferentially with macroscopic clearance, resulting in complete degloving of the penile shaft. Neurovascular bundles were preserved. The penile skin was constructed with a split thickness skin graft. Histopathological analysis of the lesion revealed an invasive and well-differentiated squamous cell carcinoma arising on a condyloma, and the surgical margins were free from tumour. The patient was staged as G2 T1 N0 M0 and was followed for one year. He did not have any erectile dysfunction and could engage in intercourse. Pelvic tomographic and physical examination findings did not reveal any episode of recurrence or metastasis. When encountering patients with giant condyloma acuminata, it should not be forgotten that it may be accompanied by squamous cell carcinoma. In addition, tissue excision should be as extensive as possible while keeping in mind the importance of the function. This is the first case of a penile-degloving surgery for giant penile condyloma, supporting conservative and preserving penile surgery for such tumours.